(3HQGAGJ GdGNJQGY aj GdUfGYGJ GdOhGFjI (B:s (3GdJfXje GdbGfhfj ddJQGNjU (B: (3GdGJaGbjI aj VhA efXeI GdJLGQI GdYGdejI (BW. T. O = Patents in the pharmaceutical industry : regulation. of contractual licenses : in the light of the (W. T. O) /s - (3SeGhj, Qje SYhOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jfbSe gPG GdcJGH Edj HGHjf hJe JbSje cd HGH Edi KdGKI aUhd JfGhd aj GdHGH GdChd CKQ EfVeGe GdCQOf defXeI GdJLGQI GdYGdejI hNGUI EJaGbjI GdLhGfH MjK JWQb aj GdaUd GdChd Edi GdJYQja HefXeI GdJLGQI GdYGdejI hEJaGbjI JQHS, haj GdaUd GdKGfj Edi EfaGP CMcGe EJaGbjI JQHS aj eLGd GdUfGYGJ GdOhGFjI MjK JfGhd GdJYQja HHQGAI GdENJQGY hTQhWgG GdehVhYjI habG ddbGfhf GdCQOfj hEJaGbjI JQHS haj GdaUd GdKGdK JfGhd BdjI GdMO ef EMJcGQ GdeYGQa GdUjOdGfjI deOI YTQjf YGeG, hbSe GdHGH GdKGfj Edi KdGKI aUhd JfGhd aj GdaUd GdChd GdJYQja HYbO GdJQNjU HESJZdGd HQGAI GdENJQGY hGdWHjYI GdbGfhfjI Ke JfGhd aj GdaUd GdKGfj CMcGe YbO GdJQNjU ef MjK EHQGeg hTQhW UMI GdJQGVj hTQhW eVehf YbO GdJQNjU Ke eQMdI GdeaGhVGJ hGdYbO GdLRFj hGdeSDhdjI GdeOfjI GdfGLeI Yf GdENdGd aj eQMdI GdJaGhV hHWdGf GdTQhW GdJbjjOjI GdefGajI ddefGaSI GdeTQhYjI, hJfGhd aj GdaUd GdKGdK BKGQ YbO GdJQNjU HUhQI Mbhb hEdJRGeGJ JbY Ydi YGJb GdeQNU hCNjQG hGdeQNU dg(B.s
(3JUeje hENQGL (B: (3GdKbGaI ddfTQ hGdJhRjY(B.s
(3GdCUd CWQhMI (B((3OcJhQGg(B)-(3LGeYI YeGf GdYQHjI ddOQGSGJ GdYQHjI, GdCQOf(B.s
(3HHdjhLQGajI (B: (3UaMI (B357-368.s
Keywords: (3efXeI GdJLGQI GdYGdejIs; (3HQGAGJ GdGNJQGYs -- (3bhGfjf hJTQjYGJs; (3GdCOhjIs -- (3bhGfjf hJTQjYGJs